2019
DOI: 10.1177/1179554918821314
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-ligand 1 Expression With Clone 22C3 in Non-small Cell Lung Cancer: A Single Institution Experience

Abstract: BACkgRouND: In recent years, the anti-programmed cell death 1 (PD-1) drug pembrolizumab (Keytruda) was approved for treatment of unresectable advanced non-small cell lung cancer (NSCLC) as first-or second-line therapy depending on the clone 22C3-programmed death-ligand 1 (PD-L1) immunohistochemical expression score by the companion diagnostic assay. We herein evaluated 22C3-PD-L1 expression of NSCLC in a single institution experience and compared it with clinicopathologic features. MATERIALS AND METhoDS: We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This study indicated that large tumor size and CT texture of pSD in LUAD were correlated with high PD-L1 expression, consistent with the results of previous studies [13][14][15]. Furthermore, large tumor size and pSD of LUAD also indicated high Ki67 expression, suggesting a relationship between the expressions of Ki67 and PD-L1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study indicated that large tumor size and CT texture of pSD in LUAD were correlated with high PD-L1 expression, consistent with the results of previous studies [13][14][15]. Furthermore, large tumor size and pSD of LUAD also indicated high Ki67 expression, suggesting a relationship between the expressions of Ki67 and PD-L1.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that the expression of PD-L1 was correlated with male smoking, high Ki67 expression, and wild-type EGFR in LUAD. Q. Zhu et al also revealed an association of PD-L1 with male gender and smoking history, supported by several other studies [14,16,17,29,30]. Q. Chen et al revealed that EGFR-mutated patients showed relatively lower PD-L1 expression than wild-type patients [17] Furthermore, it has been repetitively indicated that EGFR wild-type tumors were significantly more likely to express PD-L1 than EGFR-mutated tumors [13,17,18,[31][32][33].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The frequency of PD-L1 ≥ 50% was 26.0-34.0% in previous pivotal studies and 29.0% in a single-center study in Japan. 12,14,29 In our study, the proportion of PD-L1 ≥ 50% in the overall analysis set was 32.1%, whereas the proportion of PD-L1 ≥ 50% in the cachexia group was as high as 48.0%. Considering the possibility of selection bias caused by assessing the PD-L1 TPS only in patients with NSCLC who received chemoimmunotherapy, we assessed the PD-L1 TPS in patients with NSCLC who received chemotherapy in a single center.…”
Section: Discussionmentioning
confidence: 47%
“…Further limitations include the fact that dynamic, real-time detection of PD-L1 content in vivo is not possible, and there is also controversy surrounding the use of archived vs. fresh specimens for testing. Takeda et al evaluated the expression of PD-L1 in archived and fresh samples and found that it was significantly lower in archived specimens 79 . However, the KEYNOTE-010 trial 80 and the FIR study 81 demonstrated that either fresh or archived tissues could be reliably assessed for PD-L1 status by IHC.…”
Section: Detection Methodsmentioning
confidence: 99%